2016
DOI: 10.3109/17453674.2016.1151292
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disease as a risk factor in fast-track hip and knee replacement

Abstract: Recent studies suggest that patients with psychiatric disorders tend to do worse than patients without a psychiatric diagnosis when undergoing total hip arthroplasty (THA) or total knee arthroplasty (TKA). Whether this is due to their psychiatric condition, pharmacological treatment, a combination of the two, or something else has not been thoroughly analyzed—and there are no internationally accepted guidelines for perioperative management of psychiatric patients. This overview summarizes our current knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 61 publications
1
28
0
1
Order By: Relevance
“…However, an increased focus on preoperative risk-factors is required to define strategies for further reduction of postoperative morbidity (4,5,6). In this context, psychiatric conditions and/or psychopharmacological treatment has been demonstrated as important riskfactors for prolonged LOS, readmissions and morbidity in the fast-track THA and TKA setting (7,8,9). Although psychopathology and psychopharmacological medications may independently or collectively contribute to suboptimal outcome, unhealthy lifestyle choices, poor health care access or utilization (10) may also increase perioperative risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an increased focus on preoperative risk-factors is required to define strategies for further reduction of postoperative morbidity (4,5,6). In this context, psychiatric conditions and/or psychopharmacological treatment has been demonstrated as important riskfactors for prolonged LOS, readmissions and morbidity in the fast-track THA and TKA setting (7,8,9). Although psychopathology and psychopharmacological medications may independently or collectively contribute to suboptimal outcome, unhealthy lifestyle choices, poor health care access or utilization (10) may also increase perioperative risk.…”
Section: Introductionmentioning
confidence: 99%
“…Although psychopathology and psychopharmacological medications may independently or collectively contribute to suboptimal outcome, unhealthy lifestyle choices, poor health care access or utilization (10) may also increase perioperative risk. However, psychiatric comorbidity is often neglected in the preoperative assessment (11) and no official guidelines exist on perioperative management of the psychiatric patients (8). In this overview Gylvin et al (8) have identified a dilemma between diagnosing patients with mental disorder according to ICD-10 (12) and assessing the current symptomatology by patient-reported outcome measures (PROMS).…”
Section: Introductionmentioning
confidence: 99%
“…A few variables are known to negatively influence postoperative patient satisfaction, including high severity and chronicity of pain, quadriceps strength, marked functional limitations, the presence of psychological disease and other co-morbid conditions, and poor coping strategies. [8][9][10] However, these measures are mostly subjective and difficult to obtain and interpret. Therefore, searching for objective measures that can be more easily interpreted may prove more helpful in preoperative decision-making.…”
mentioning
confidence: 99%
“…Furthermore, psychiatric patient may have a potential risk of postoperative artificial joint dislocation [14]. Gylvin et al described that pre-existing psychological factors have an effect on the outcome of arthroplasty and appropriate strategies might be needed [15]. Tsukada et al reported the lower dislocation rate following THA via Direct Anterior Approach (DAA) than via posterior approach (PA).…”
Section: Discussionmentioning
confidence: 99%